Rheology and mechanical aspects of a self-compacting soil-cement in the fresh state - Morais Alcantara, Marco Antonio de [UNESP]; Barbosa Nunes, Sandra Conceicao; Meneses Espinheira Rio, Joao Filipe; Lima, Dario Cardoso de (Univ Fed Rio De Janeiro, Lab Hidrogenio, 2017)
The article presents a study of design parameters for the fresh self-compacting soil-cement so that it can be framed under the action of its own weight in the production of prefabricated elements. In the experimental work, it was used a residual soil of the region of Porto, Portugal, Portland cement, water and an additive of steric and electrostatic actuation as superplasticizer. The proportion of materials were related to soil dry weight with cement contents ranging from 20, 25, and 30%, water from 41, 44 and 47%, and superplasticizer from 0.66, 0.84 and 0.93%. The tests performed on fresh state fit into assessment protocols used for self-compacting mortars and concretes, and refer to the spreading test using a mini cone and the flow test with the aid of a funnel. In the hardened state, it was performed the unconfined compression test. The results indicated that the fresh self-compacting soil-cement falls technologically into the behavior observed in concretes and mortars, distinguishing the expressive influence of water and superplasticizer as fluidity agents, and soil and cement as viscosity controlling agents. Amounts of these constituents were defined in order to better optimize the conditions of fluidity and mobility of the mixtures, which may have as primary parameter of dosage the water/cement ratio, with regard to mechanical strength, and the specimens apparent density. The properties of fluidity and mobility are preferably correlated with the water/(cement+soil) ratio.
Keywords: self-compacting soil-cement; unconfined compression strength; rheology